Not Ideal, But Still Acknowledged: A 10-Country Survey on Empathy for Victims of Anti-LGBT Violence - Godzisz, Piotr (Journal of interpersonal violence, 2023)
Using data from a cross-national survey conducted on representative samples of populations from 10 European countries (n = 10,766), the present study is the first one to empirically measure the validity of Christie’s influential ideal victim model. We use a range of scenarios built around common types of anti-LGBT violence to verify the extent to which the public’s empathy for victims is contingent on the victim’s identity and the circumstances of the crime. The results provide strong evidence that, when applied to this group of victims, the rules of the ideal victim work, adequately moderating the public’s emotional reactions. We found that all victims receive relatively high levels of empathy, but the further the victim is from the ideal, the less support they can count on. Thus, even though no victim is “rejected,” a clear hierarchy of victimization emerges. As a group, LGBT people suffer from an empathy deficit, but there also are considerable variations within this group, with a lesbian attacked by extremists receiving the most, and a drunk transgender person receiving the least empathy from the public. The study contributes to the development of theory by embedding the ideal victim model in a broader sociological paradigm of dramaturgical analysis. Since our research shows that the victim’s LGBT status decreases the levels of empathy (being seen as a type of stigma), we call for more attention to be paid to the actor’s identity in Goffman’s framework. Implications for practice and further research are offered.